The Concept of Food and Energy Sovereignty in the Film "Pesta Babi" Regarding the Rate of Deforestation in Papua's Forests and Ecological Implications - Aditya Vilareal; Hidayahtullah; Keyza Okta; Melania Meirelda; Dodit Ardiatma (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to analyze the rate of deforestation in Papua and its ecological implications, using the documentary film "Pesta Babi" as a medium for ecological representation and critique. Massive deforestation in Papua, primarily due to food estate projects, oil palm plantation expansion, and mining, has threatened the food and energy sovereignty of indigenous communities. A qualitative approach using media text analysis and a systematic literature review was used in this study. The analysis shows that the forced conversion of indigenous forests not only eliminates traditional biomass-based food and energy sources but also marginalizes local communities, triggers biodiversity loss, and contributes to the global climate crisis. In conclusion, a review of forest management policies that position local communities as rights-holders is needed to reduce the rate of deforestation, protect the food and energy sovereignty of indigenous communities, and prevent natural colonialism.